Plant cultivation as an educational tool for the transformation of quality of life - Souza, Caroline Almeida; Velasco, Giuliana Del Nero; Amaral, Raquel Dias de Aguiar Moraes; Solera, Maria Lucia (Revista Hipótese, 2019)
The article presents the experience of using plant knowledge as an interdisciplinary tool to promote landscape transformation and improve the quality of life. Participatory workshops held at CEU Três Pontes addressed the theme of plant cultivation. Participants understood their ability to change the environment in which they live using their knowledge on plant and its cultivation. The theme addressed in the workshops can be incorporated into many disciplines of the elementary school curriculum.
Keywords: Environmental education; Empowerment; National Common Curricular Base. Objectives of sustainable development; Interdisciplinarity